Enhancing flame flashback resistance against Combustion Induced Vortex Breakdown and Boundary Layer Flashback in swirl burners. (15th November 2018) - Hatem, F.A.; Alsaegh, A.S.; Al-Faham, M.; Valera-Medina, A.; Chong, C.T.; Hassoni, S.M.
Highlights: Properly positioned central injection with microsurfaces reduce flashback propagation. Position of central air injection impacts on turbulence, thus flashback trends. Microsurfaces reduce BLF propagation and impact on onset of coherent structures. Wider, stable operation is achieved by reducing CIVB and BLF flashbacks simultaneously. The combined technique can increase operability and flexibility, and reduce maintenance. Abstract: Swirl combustors have proven to be effective flame stabilisers over a wide range of operation conditions thanks to the formation of well-known swirl coherent structures. However, their employment for lean premixed combustion modes while introducing alternative fuels such as high hydrogenated blends results in many combustion instabilities. Under these conditions, flame flashback is considered one of the major instability problems that have the potential of causing considerable damage to combustion systems hardware in addition to the significant increase in pollutant levels. Combustion Induced Vortex Breakdown is considered a very particular mode of flashback instability in swirling flows as this type of flashback occurs even when the fresh mixture velocity is higher than the flame speed, a consequence of the interaction between swirl structures and swirl burner geometries. Improvements in burner geometries and manipulation of swirling flows can increase resistance against this type of flashback. However, increasing resistance against Combustion Induced Vortex Breakdown can lead to augmentation in the propensity of another flashback mechanism, Boundary Layer Flashback. Thus, this paper presents an experimental approach of a combination of techniques that increase Combustion Induced Vortex Breakdown resistance, i.e. by repositioning a central injector and using central air injection, while simultaneously avoiding Boundary Layer Flashback, i.e. by changing the wall boundary layer characteristics using microsurfaces on the nozzle wall. Results show that using these techniques together has promising potentials regarding wider stable operation for swirl combustors, enabling them to burn a broader variety of fuel blends safely, while informing developers of the improvements obtained with the combined techniques.